Storage effect on the shear bond strength of adhesive systems - Konno Alysson Noriyuki Kajishima; Sinhoreti Mário Alexandre Coelho; Consani Simonides; Sobrinho Lourenço Correr; Consani Rafael Leonardo Xediek (Fundação Odontológica de Ribeirão Preto, 2003)
The purpose of this study was to evaluate the effects of storage (1 day, 3 months and 6 months) on the shear bond strength of five adhesive systems on bovine dentin substrate. One hundred and fifty bovine incisors were flattened until areas of a minimum of 5 mm in diameter were exposed. A round area of 4 mm in diameter was marked on the dentin to be treated with the following adhesive systems: Clearfil Liner Bond 2V (CLB2V), Scotchbond Multi Purpose Plus (SBMP), Optibond Solo (SOLO), Prime & Bond NT (PBNT) and Etch & Prime 3.0 (E&P). To perform the test, a composite restoration (Z100) was made in a cylindrical shape on the treated surface. After the storage period in distilled water at 37ºC, the samples were tested on an Instron testing machine. Results were submitted to ANOVA and Tukey's test at 5% significance level. SBMP, PBNT and E&P were statistically similar at all storage times (p>0.05). CLB2V demonstrated the highest mean shear bond strength at 3 months which was not significantly different at 6 months (p>0.05). In addition, CLB2V had the highest means at all times tested. SOLO had the lowest mean shear bond strength at 6 months, which was statistically lower than means at 3 months and 1 day (p<0.05).